Antioxidant properties of hidazepam and amitriptyline with pain syndrome of rats - Yu. I. Gubskiy; N. M. Seredynska; T. A. Buchtiarova; L. P. Babenko (The State Expert Center of the Ministry of Health of Ukraine, 2019)
Peroxide modification of cell biostructures and functions due to the activation of free radical oxidative processes underlies the pathogenesis of a significant number of diseases different in its etiology. The ability of pharmacological drugs which have antioxidant properties inhibit free radical peroxide oxidation and stabilize the structure and function of cell membranes and thus create optimal conditions for the preservation of homeostasis of cells and tissues. It makes pathogenetically grounded their widespread using in medical practice. Therefore, it was expedient to study the effect on the state of lipid peroxidation in the case of the development of the pain syndrome of drugs which are used during anesthesia as an adjuvant. For the study, drugs from the group of psychotropic drugs were selected as adjuvants. This is due to that pain syndromes of the different origin often cause psycho-emotional disorders. In addition, pain is not only a symptom of many acute and chronic diseases but also a complex psycho-physiological phenomenon which involves the mechanisms of the regulation and the formation of emotions and motor, humoral and hemodynamic reactions. The use of antidepressants in combination with other analgesics pharmaceuticals proved to be effective in placebo-controlled trials in the patients with the chronic pain syndrome. Among the drugs from the group of tranquilizers the greatest application in our time have been acquired derivatives of benzodiazepine. They are recommended for use on the background of analgesics in the case of the treatment of chronic pain syndrome in order to reduce effects of the excitement, anxiety, muscle tension, as effective and safe sleeping pills. So the purpose of the work is to study the effects of hidasepam and amitriptyline with the prophylactic and therapeutic administration on the intensity of the processes of the lipid peroxidation in serum, erythrocyte membranes, homogenate of rat spinal cord in case of the development of pain syndrome. The results of the research indicate that the development of pain syndrome caused by subcutaneous administration in the dorsal surface of the foot of the right posterior paw of the animal 0,1 ml 2% aqueous solution of formalin is accompanied by the appearance of oxidative stress in the experimental animals. In blood serum, erythrocyte membranes, spinal cord homogenates, the content of TBC-active products of the lipid peroxidation increases. Prophylactic-therapeutic administration of hidazepam per os in a dose 0,02 mg/kg of the body weight of animals prevents the development of oxidative stress in the investigated biological substances thus protecting them from damage and reducing the intensity of the pathological process. Pprophylactic and therapeutic administration of amitriptyline per os in a dose 16 mg/kg of the animals weight does not affect the intensity of the lipid peroxidation processes. The obtained results allow to optimize the treatment regimens due to the combined using of the non-narcotic analgesics and the non-steroidal anti-inflammatory drugs with the adjuvant anti-oxidant drugs from the group of the psychotropic medicines.